Are AI Diagnostic Tools Regulated in Europe? A Deep Dive into the Dual Framework of MDR and the AI Act - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid integration of Artificial Intelligence AI into healthcare, particularly in diagnostic tools, promises a revolution in patient care. From analyzing ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care